Prevalence of Tobacco Consumption among Men in Amarpur Village, Uttar Pradesh, India, May 2019: A cross-sectional study - Ali Jan Nazari; Naveen H Simon; Ajoke Akinola; Muskan Kaushik (Wolters Kluwer Medknow Publications, 2020)
Background: Globally, there are over 7 million deaths resulting from tobacco consumption with 1 million deaths in India per year, and among middle-income countries listed as the second major consumer of tobacco products. The prevalence of tobacco consumption according to the recent studies already done is dissimilar among gender, different age categories, religion, urban and rural areas. The study purpose was to assess the prevalence of tobacco consumption among rural men. Methodology: Community-based cross-sectional study conducted from December 2018 to May 2019 in Amarpur village, Uttar Pradesh, India. There were 244 men in the age group of 15-54 years old, selected for the survey. Purposive sampling technique was used for taking sample and SPSS 16 software for statistics analysis. Results: The prevalence of smoked and smokeless tobacco was 36.1% and 42.6%. The most prevalent form of tobacco among smoked form was bidi and hookah, while among smokeless forms were gutka with paan. Among the smokers, 69.3% were willing to quit smoking on smokeless consumers and 78.8% were willing to stop tobacco consumption at some point. Age, marital status, education, and the number of children were associated with tobacco smoker and chewer. Tobacco was highest 38 (48%) among 25-34 years of age for tobacco smoker with P = 0.002, and tobacco chewer highest among 35-44 years which was 34 (61.8%) with P = 0.000. About one-third of the patients do not know that tobacco intake has ill effect on their health; the most common influencing factors for tobacco use were for enjoyment and stress. Conclusion: Prevalence of tobacco consumption was high in this community. Urgent awareness and increased literacy needed to improve knowledge on the effect of smoking in the rural area. Through the development of effective health education and multi-factorial quitting strategies to help those who are willing to quit tobacco.